2006
DOI: 10.1017/s0025315406014457
|View full text |Cite
|
Sign up to set email alerts
|

Diel variation in sea grass dwelling shrimp: when to sample at night?

Abstract: The present study investigates hourly variation in nocturnal abundance fluctuations in a tropical, Caribbean sea grass bed. As expected, results indicate that significant diel variation is present. In addition all dominant species show an abundance peak shortly after sunset, with numbers gradually declining throughout the night. It is therefore suggested that nocturnal samples are not only incorporated into any sampling regime, but that nocturnal samples are taken within two hours after sunset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In both of these sites, the most abundant species was Latreutes fucorum (Fabricius, 1798) (Hippolytidae) (Bauer, 1985a,b;De Grave et al, 2006). In our study, the dominant species include Hippolyte obliquimanus and Latreutes parvulus (Hippolytidae).…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…In both of these sites, the most abundant species was Latreutes fucorum (Fabricius, 1798) (Hippolytidae) (Bauer, 1985a,b;De Grave et al, 2006). In our study, the dominant species include Hippolyte obliquimanus and Latreutes parvulus (Hippolytidae).…”
Section: Discussionsupporting
confidence: 46%
“…Push net samplings, similar to the one we used, have found richness of 23 species in Puerto Rico (Bauer, 1985a,b) and of 14 species in Honduras (De Grave et al, 2006). In both of these sites, the most abundant species was Latreutes fucorum (Fabricius, 1798) (Hippolytidae) (Bauer, 1985a,b;De Grave et al, 2006).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Caridean shrimps are important faunal components of temperate and tropical seagrass meadow ecosystems (e.g. Kikuchi 1962Kikuchi , 1966Bauer 1985Bauer , 1989Bauer , 2004De Grave et al 2006). Considerable temporal variation in breeding patterns occurs in caridean species.…”
Section: Introductionmentioning
confidence: 99%
“…Caridean shrimps are often a dominant faunal group in seagrass beds and include carnivorous and herbivorous species (Heck 1977;Saloman 1979;Gore et al 1981;García Raso et al 2006;Unsworth et al 2007). Shrimps are an important link between primary production and higher trophic levels (Kikuchi 1966;De Grave et al 2006;Unsworth et al 2007). Studies using nocturnal sampling have shown that carideans of the family Processidae may be abundant in seagrass meadows (Kikuchi 1962(Kikuchi , 1966Leber 1983;Bauer 1985;De Grave et al 2006).…”
Section: Introductionmentioning
confidence: 99%